Articulating New Zealand and literature in "New Zealand literature" classes: Attending to the parergon. Issue 2 (3rd March 2020) - Prentice, Chris
ABSTRACT: With the increasing globalization of tertiary education through international study abroad and university exchange schemes, New Zealand literature classes are today increasingly likely to be taught to diverse groups of students from different countries and ethnicities. How might this affect the framing of courses, texts chosen for study, and the conversations that take place in the classroom? Yet with the greater diversity of the New Zealand population, and as New Zealand students increasingly identify as subjects of a globalized world, any opposition between local and global perspectives breaks down. Following a discussion of recent debates about the institution of "New Zealand literature" in the context of globalization, this article turns to particular examples of New Zealand literature undergraduate university courses. It adopts the critical lens of Derrida on the parergon to show how "New Zealand literature" is the product of, and at the same time always disturbed by, its framing.